2015
DOI: 10.1111/hpb.12368
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of hepatectomy for hepatocellular carcinoma with bile duct tumour thrombus

Abstract: A major hepatectomy, extrahepatic biliary resection and hepaticojejunostomy should be the standard for HCC with BDTT, and long-term survival is possible after radical surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 27 publications
2
56
0
Order By: Relevance
“…7,8,12 In our current series, the 5-year survival rate of HCC patients with BDTT was 36.6%, and there was no significant difference in survival between HCC patients with or without BDTT when the two groups were matched by stage. Wong et al also reported that HCC patients with or without BDTT demonstrated similar survival rates using their matching criteria.…”
Section: -8 Yeh Et Al Reported the Relationship Between The Pathogenmentioning
confidence: 46%
See 3 more Smart Citations
“…7,8,12 In our current series, the 5-year survival rate of HCC patients with BDTT was 36.6%, and there was no significant difference in survival between HCC patients with or without BDTT when the two groups were matched by stage. Wong et al also reported that HCC patients with or without BDTT demonstrated similar survival rates using their matching criteria.…”
Section: -8 Yeh Et Al Reported the Relationship Between The Pathogenmentioning
confidence: 46%
“…Wong et al also reported that HCC patients with or without BDTT demonstrated similar survival rates using their matching criteria. 7 Macrovascular invasion, including portal vein invasion and hepatic vein invasion, is correlated with poor prognosis in HCC patients. [13][14][15][16][17] Regarding BDTT, in contrast, Esaki et al reported that macroscopic bile duct invasion demonstrates a favorable impact on patient outcomes in HCC patients with BDTT.…”
Section: -8 Yeh Et Al Reported the Relationship Between The Pathogenmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found many risk factors of the recurrence of hepatocellular carcinoma after resection, including hepatitis B virus infection, tumor diameter, tumor number, tumor capsule, vascular invasion, portal vein tumor thrombus, surgical margin width, intraoperative bleeding and blood transfusion. [9][10][11] It has been reported that 1-year and 2-tear recurrence rates of HCC in our country are 38.7% and 57.9%, respectively. 12 In this study, 1-year and 2-tear recurrence rates of patients with HCC in caudate lobe were 44.4% and 88.9%, significantly higher than average recurrence rate as mentioned above, suggesting that the prognosis of surgical treatment of HCC in the caudate lobe is worse than that of HCC in other parts of liver, consistent with the results of similar studies.…”
Section: Discussionmentioning
confidence: 99%